Linking root carbon molecular diversity to arbuscular mycorrhizal fungi community niche differentiation for soil aggregation in maize-soybean intercropping systems - Xingyu Guo; Suqi Lin; Mengkai Wang; Chuanqin Huang; Mingxia Wang; Wenfeng Tan (Soil and Tillage Research, 2026)

A universal chemical strategy towards the use of diluent for carbonate localized high-concentration electrolytes - Qingjiang Liu; Min Niu; Xingyu Chen; Zongfan Yang; Yan Meng; Yi-Bing Wang; Xian-Xin Feng; Liwei Dong; Lin Mei; Libao Chen; Changsong Dai; Bo Song; et al. (Chemical Engineering Journal, 2026)

Thermal-safety response and gas-generation characteristics of high-nickel ternary/silicon-carbon semi-solid-state batteries prepared with different curing times - Chunjing Lin; Qingsong Zhang; Xingyu Pan; Shiqiang Liu; Hongtao Yan; Fang Wang (Process Safety and Environmental Protection, 2026)

Settling by water: Human habitation adapted to landscape evolution at the Xuecheng site in the lower reaches of the Yangtze River during the Mid-late Holocene - Zhiping Zhang; Zhujun Hu; Xingyu Zhou; Hui Peng; Jue Sun; Jiahao Xu; Hongwei Shi; Lin Yang; Ping Zhang; Feng Xu; Harry F. Lee; Xin Jia (Science China Earth Sciences, 2026)

A SERS-active swab for integrated sampling, response and detection of saliva of normal and sleep-deprived mice - Xingyu Wu; Yuchuan Wang; Jinfeng Lin; Tingyu Zhang; Yang Wang; Jian Dong (Analytica Chimica Acta, 2026)

A synergistic strategy combining passive insulation and active discharge for mitigating thermal runaway propagation in lithium-ion batteries - Peng Liu; Xingyu Long; Tao Cao; Jiayi Ge; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2026)

Dual-stream cross-modal networks for acoustic-visual detection of surface vessels on wave gliders - Jianxin Wu; Hongqiang Sang; Jiawei Jiang; Xingyu Zhang; Chao Wang; Ying Zhou; Lin Zhang; Xiujun Sun (Ocean Engineering, 2026)

Remote sensing image dehazing for maritime object detection: A physics-driven and frequency-aware network - QingXin Tang; Xingyu Liu; Qin Lin; Hongxiang Feng (Ocean Engineering, 2026)

Ear-layer between-row leaf azimuthal orientation is associated with canopy crowding status and vertical light distribution in high-density maize - Ziqing Lin; Jiawang Lin; Xingyu Zhong; Yong Tang; Bin Lei; Guodong Wang; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

In situ trophic modes and metabolic traits of the dinoflagellate Karenia in response to short-term localized warming - Hao Zhang; Xiao Ma; Shufei Zhang; Lingshuai Zhang; Chenhui Xiang; Zhiqin Wang; Lin Zhu; Bowei Gu; Xingyu Song; Honghui Huang; Lijuan Long; Xiaomin Xia (Marine Pollution Bulletin, 2026)

Engineering molecular confinement: Confined nucleic acid technology with porous hydrogels and its applications in food science - Tao Yang; Yiting Lin; Xingyu Lin; Jing Zhang; Zisheng Luo (Trends in Food Science & Technology, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Nighttime apple harvesting image enhancement based on a global–local feature fusion diffusion model - Liuchang Xu; Ting Ni; Fangshuo Zhou; Qingming Lin; Luyao Chen; Qianqian Luo; Kai Xia; Xingyu Xue; Xinyu Zheng; Sensen Wu; Zhenhong Du; Kai Fang; et al. (Computers and Electronics in Agriculture, 2026)

Seamless Task Scheduling for Vehicle-Crane Coordination in Container Terminals: A Spatio-Temporal Optimization Approach - Xingyu Wang; Xiangwei Liu; Jintao Lai; Weimeng Lin; Qiang Ling; Yang Shen; Ning Zhao; Jia Hu (Journal of Marine Science and Engineering, 2026)
Task scheduling for vehicle–crane coordination is crucial for the operational efficiency of electrified automated container terminals (ACTs). However, under fully shared dispatching, existing studies rarely capture how charging-induced capacity fluctuations disrupt bidirectional service–arrival matching and propagate service-window shifts. To address this gap, this study proposes a comprehensive spatio-temporal optimization approach. Firstly, a bi-objective model is established to minimize service–arrival mismatch and vehicle energy consumption under state-of-charge (SOC) and charger-capacity constraints, explicitly quantifying vehicle–crane alignment at both handling interfaces. Secondly, an enhanced multi-objective algorithm (ST-NSGA-II) is developed, integrating a feasibility-preserving recursive decoding mechanism and a spatio-temporal variable neighborhood search (VNS) procedure. Finally, numerical experiments demonstrate that ST-NSGA-II significantly reduces mismatch and energy consumption compared to standard NSGA-II in large-scale scenarios. It also outperforms MOEA/D in Pareto-set quality, yielding a higher hypervolume (1.301 vs. 0.960) and a lower Spacing value (0.102 vs. 0.185). The results demonstrate that the proposed spatio-temporal optimization approach can effectively reduce handover mismatch compared to conventional scheduling modes, thereby achieving seamless task scheduling for vehicle–crane coordination.

Lactate-driven histone lactylation enhances GDF15 secretion in skeletal muscle under mtDNA mutation-induced mitochondrial stress - Yan Lin; Busu Li; Jiayin Wang; Weiyue Si; Xingyu Zhuang; Ying Zhao; Wei Jiang; Wei Wang; Dongdong Wang; Fuchen Liu; Ruonan Duan; Yuying Zhao; et al. (Science Bulletin, 2026)

Artificial intelligence films for dynamic and sustainable preservation of high-value fruits - Zhaoxuan He; Shenggui Lin; Xingyu Liu; Wenqian Li; Yanyong Mao; Hao Shi (Food Research International, 2026)

Brazide: A breakthrough plant growth regulator that delays leaf senescence under heat stress to promote grain yield in winter wheat (Triticum aestivum L.) - Xingyu Zhong; Qihua Wu; Le Yang; Ziqing Lin; Dan Ren; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2026)

BMSC vesicles-encapsulated tannic acid-derived carbon dots efficiently target and orchestrate mitochondria mitophagy to promote cartilage repair in osteoarthritis - Rongjie Lin; Zhusong Huang; Weibin Chen; Quan Liu; Huiling Guo; Xingyu Lin; Yao Wang; Zhenbin Chen; Xi Zeng; Shishui Lin; Shaohuang Weng; Min Chen (Chemical Engineering Journal, 2026)

Multifunctional Fe-melatonin nanozyme facilitates osteoporotic bone regeneration based on a mitochondrial protection and microenvironment remodeling strategy - Xiaojing Li; Ya Cui; Liyun Wang; Xingyu Zhou; Jiaqiang Liu; Lingyue Shen; Kaili Lin; Lixia Mao (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

The effect of combined treatments of heat-moisture and enzyme on the texture, cooking and in vitro digestibility qualities of rice noodles - Xingyu Chen; Yang Yang; Jiayi Xu; Huaxi Xiao; Qinlu Lin; Jiangtao Li; Yejia Liu (Journal of Cereal Science, 2026)

Characterization and structural analysis of a novel glucurono-xylanase from Chaetomium fimeti and its potential application in pear juice clarification - Xingyu Liu; Lin Han; Mengqi Liu; Jinglei Wu; Dandan Zhao; Huan Rao; Xia Zhao; Xuechao Zheng; Jianxiong Hao; Xueqiang Liu (Food Research International, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Explainable deep learning combined attention-based LSTM for building energy prediction: a framework from the perspective of supply side - Muhammad Saad Ul Haq; Wenjie Ji; Xingyu Pei; Shuli Liu; Yang Geng; Borong Lin; Haider Ali (Energy and Buildings, 2026)

Electrochemical synthesis of ultra-compact gold hexagonal nanostar substrate for enhanced and stable SERS detection - Jingjing Wang; Waqas Ahmad; Yuzhen Liang; Yi Xu; Tianhui Jiao; Peipei Qi; Xingyu Lin; Quansheng Chen (Analytica Chimica Acta, 2026)

White light-excited B and N Co-doped dual-mode afterglow carbon dots with long lifetime and high quantum yield - Yingying Zhao; Xingyu Liu; Xingmei Li; Jingxia Zheng; Lin Chen; Yongzhen Yang; Xuguang Liu (Chemical Engineering Journal, 2025)

Two wins in one move of additive engineering: Achieving crystallization regulation and multi-site defect passivation for high-performance perovskite solar cells - Xinyue Song; Yikun Hua; Jie Zhang; Lei Zhao; Chao Wu; Weiyuan Chen; Xingyu Gao; Lin Song (Chemical Engineering Journal, 2025)

Nano-sized heterogeneous photocatalyst Fe3O4@V/TiO2-catalyzed synthesis and antimycobacterial evaluation of 2-substituted benzimidazoles - Lijian Bao; Xiaodong Chen; Yanli Li; Guangyuan Zhu; Jingjun Wang; Mingyue Chen; Xingyu Bian; Qiang Gu; Yumin Zhang; Feng Lin (Molecular Diversity, 2025)

Generative Model Enhanced X-ray Computed Tomography Imaging for Pharmaceutical Powder Microstructure Reconstruction and Evaluation - Leqi Lin; Xingyu Zhou; Yuetong Ding; Guangyao Lyu; Xizhong Chen (AAPS PharmSciTech, 2025)

Experimental investigation and mechanism analysis of mitigating thermal runaway propagation in lithium-ion battery modules by high-rate discharge - Peng Liu; Xingyu Long; Kuijie Li; Wenhao Zhu; Gang Wu; Lin Hu (Process Safety and Environmental Protection, 2025)

HTEM: High-throughput toolkit for elasticity modeling - Zhen Yang; Jiawei Xian; Yuanji Xu; De-Ye Lin; Qingchun Wang; Xingyu Gao; Fuyang Tian; Haifeng Song (Computer Physics Communications, 2025)

Reconfiguration of the Fe N4 active site by S element and its effect on hydrogen evolution performance of Fe‑carbon dots SACs - Chenfang Lou; Qinfen Tian; Jiaqi Liang; Tingfeng Lin; Jiande Lin; Xinru Zheng; Xingyu Chen; Xin Li; Guofa Dong; Yuan Hu; Jiandong Zhuang (Chemical Engineering Journal, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Contrasting short-term dynamics of supraglacial ponds along the Hindu Kush-Himalaya revealed by PlanetScope imagery and deep learning - Xingyu Xu; Lin Liu; Lingcao Huang; Yan Hu; Guoqing Zhang; Adina Racoviteanu; Emily Victoria Liu; YingTo Agnes Chan (Global and Planetary Change, 2025)

Regulating the coordination distance of solvation structure for high-performance aqueous zinc ion batteries - Yijia Luo; Chao Li; Lieyuan Zhang; Xin Tan; Yi Yang; Bin Xie; Dandan Zhang; Haoran Lang; Xingyu Chen; Xuemei He; Qiaoji Zheng; Xinqiao Wu; et al. (Chemical Engineering Journal, 2025)

DeepSeek-LLM with Adaptive RAG for Pharmaceutical Dissolution Prediction - Leqi Lin; Xingyu Zhou; Kaiyuan Yang; Yang Liu; Xizhong Chen (Pharmaceutical Research, 2025)

Implications for environmental management: assessing urban ecological environment quality in Chengdu with a modified remote sensing ecological index - Fengheng Sun; Shengwei Zhao; Xiao He; Xingyu Lin; Li Wang; Zhanbiao Yang (Environmental Monitoring and Assessment, 2025)

Superlinear control of phosphorus recycling in coastal sediments by organic matter availability - Jing Sun; Xiaotian Zhou; Yuxuan Lin; Xingyu Yang; Liuqian Yu; Charmaine C.M. Yung; Qiong Zhang; Jiying Li (Water Research, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

Ultrasmall nanochannel-coated photoelectrode for confined photoelectrocatalysis of patulin in complex food matrix without affecting nutrition - Wenyan Yan; Zisheng Luo; Jiayi Liu; Xianfeng Peng; Zhenbiao Li; Xingyu Lin (Chemical Engineering Journal, 2025)

Efficient three-dimensional electrochemical degradation of alizarin red by CeO2−MnO2/NF particle electrode synergized with ozone - Ke Hu; Fangyuan Zhao; Faqin Dong; Xingyu Zhang; Lin Zhou; Ming Guo (Journal of Environmental Sciences, 2025)

Rethinking electrification strategy for China's passenger vehicle fleet decarbonization in resource-constrained environments - Xingyu Xue; Yin Li; Guorui Jia; Frank T. Hong; Zhenhong Lin; Chen Liu (Resources, Conservation and Recycling, 2025)

Sensitivity-enhanced hydrogel digital RT-LAMP with in situ enrichment and interfacial reaction for norovirus quantification in food and water - Tao Yang; Liang Xue; Zisheng Luo; Jianhan Lin; Xinyang Zhang; Fangbin Xiao; Yuanjie Liu; Dong Li; Xingyu Lin (Journal of Hazardous Materials, 2025)

Exosome-loaded methacrylated silk fibroin hydrogel delays intervertebral disc degeneration by DKK2-mediated mitochondrial unfolded protein response - Xiao Lu; Zhidi Lin; Liujingzhou Li; Guangyu Xu; Dachuan Li; Zhaoyang Gong; Jiongdong Wu; Tian Gao; Xingyu Guo; Chenpei Xu; Xinlei Xia; Feizhou Lyu; et al. (Chemical Engineering Journal, 2025)

Investigating Catching Hotspots of Fishing Boats: A Framework Using BeiDou Big Data and Deep Learning Algorithms - Fen Wang; Xingyu Liu; Tanxue Chen; Hongxiang Feng; Qin Lin (Journal of Marine Science and Engineering, 2025)
Illegal, unreported, and unregulated (IUU) fishing significantly threatens marine ecosystems, disrupts the ecological balance of the oceans, and poses serious challenges to global fisheries management. This contribution presents the efficacy of China’s summer fishing moratorium using BeiDou vessel monitoring system (VMS) data from 2805 fishing vessels in the East China Sea and Yellow Sea, integrated with a deep learning framework for spatiotemporal analysis. A preprocessing protocol addressing multidimensional noise in raw VMS datasets was developed, incorporating velocity normalization and gap filling to ensure data reliability. The CNN-BiLSTM hybrid model emerged as optimal for fishing behavior classification, achieving 89.98% accuracy and an 87.72% F1 score through synergistic spatiotemporal feature extraction. Spatial analysis revealed significant policy-driven reductions in fishing intensity during the moratorium (May–August), with hotspot areas suppressed to sporadic coastal distributions. However, concentrated vessel activity in Zhejiang’s nearshore waters suggested potential illegal fishing. Post-moratorium, fishing hotspots expanded explosively, peaking in October and clustering in Yushan, Zhoushan, and Yangtze River estuary fishing grounds. Quarterly patterns identified autumn–winter 2021 as peak fishing seasons, with hotspots covering >80% of East China Sea grounds. The framework enables real-time fishing state detection and adaptive spatial management via dynamic closure policies. The findings underscore the need for strengthened surveillance during moratoriums and post-ban catch regulation to mitigate overfishing risks.

Towing Resistance and Design of a Towing Scheme for a Floating Wind Turbine - Pengfei Gao; Xiaobin Yuan; Shihua Liu; Wen Lin; Mingsheng Chen; Zhiqiang Wang; Yichang Tang; Xingyu Jiang (Journal of Marine Science and Engineering, 2025)
Towing operation is an important part of the transportation and installation of offshore floating wind turbines. The study of towing resistance is of great significance to the efficient construction of floating wind turbine towing. This paper takes the floating wind turbine model designed by “China Energy Construction Group Guangdong Electric Power Design Institute Co., Ltd.” as the research object, uses STAR-CCM+ 2302 software to establish the computational domain model of floating wind turbine towing, and compares it with the existing physical model experimental results and empirical formula calculation results to verify the accuracy of the CFD resistance prediction method; then the method is used to calculate the still water towing resistance of the new large-megawatt floating wind turbine at different drafts and speeds, and according to the resistance calculation results, the integrated towing system of the floating wind turbine is established in ANSYS-AQWA (Version 2023 R1), the influence of environmental loads on towing resistance is analyzed, and the selection basis of tugboat is proposed. The results show that towing resistance is closely related to the draft, speed, and foundation configuration of the wind turbine platform. In order to ensure the safety of the towing system, the speed should be kept below 4 kn. The experimental results are compared and verified that the calculation results of this method are close to the experimental values and the empirical formula calculation values, which realizes the rapid prediction of the towing resistance of the floating wind turbine and provides guidance for the towing operation of the offshore floating wind turbine platform.

Decipher syntrophies and adaptive response towards enhancing conversion of propionate to methane under psychrophilic condition - Miao Yan; Zhijian Shi; Xinjie Zhang; Xiaofeng Lin; Yongming Sun; Xingyu Cheng; Hailin Tian; Ying Li (Water Research, 2025)

Regulating crystallization kinetics in high-performance perovskites solar modules via vapor seed layer engineering - Juan Zhang; Bingchen He; Jin Huang; Lin Yang; Yian Ding; Wenjun Zhang; Yukun Guo; Lei Shi; Abuliti Abudula; Weizhi Du; Xiaogang Hao; Xiaofei Ji; et al. (Chemical Engineering Journal, 2025)

Artificial intelligence-driven quantification of antibiotic-resistant Bacteria in food by color-encoded multiplex hydrogel digital LAMP - Tao Yang; Xinyang Zhang; Yuhua Yan; Yuanjie Liu; Xingyu Lin; Wei Li (Food Chemistry, 2025)

One-step fabrication of all-in-one biocompatible polymer wrapping carbon dots for efficient atmospheric water harvesting from plants - Xianfeng Peng; Jingjing Wang; Wenyan Yan; Xingyu Lin (Chemical Engineering Journal, 2025)

Global thresholds for the climate-driven effects of vegetation restoration on runoff and soil erosion - Xi Lin; Shengwei Zhang; Xingyu Zhao; Ruishen Li; Shuai Wang; Lin Yang; Xinghui Chen (Journal of Hydrology, 2025)

Emission Estimation and Spatiotemporal Distribution of Passenger Ships Using Multi-Source Data: A Case from Zhoushan (China) - Xubiao Xu; Xingyu Liu; Lin Feng; Wei Yim Yap; Hongxiang Feng (Journal of Marine Science and Engineering, 2025)
Quantifying and estimating shipping emissions is a critical component of global emission reduction research and has become a growing area of interest in recent years. However, emissions from short-distance passenger ships operating on inter-island routes and their environmental impacts have received limited attention. This contribution investigated the temporal and spatial distribution characteristics of pollutants emitted by short-distance passenger ships at Zhoushan (China) using Automatic Identification System (AIS) data and the bottom–up emission model integrated with multi-source meteorological data. A year-long emission inventory was investigated. The results indicated that high-speed passenger ships contributed to the largest share of the emissions. The emissions were predominantly concentrated during daytime hours, with the routes between Zhoushan Island and Daishan, Daishan and Shengsi, and Zhoushan Island and Liuheng Island accounting for most of the emissions. Furthermore, intra-port waterways were identified as the primary emission areas for short-distance passenger ships. This study provides essential data support and references for the relevant authorities to understand the emission patterns of short-distance passenger ships, thereby facilitating the formulation of targeted emission reduction strategies for the maritime passenger transport sector.

Targeting modulation of intestinal flora through oral route by an antimicrobial nucleic acid-loaded exosome-like nanovesicles to improve Parkinson’s disease - Weitong Cui; Zhiyong Guo; Xingyu Chen; Ran Yan; Wenjuan Ma; Xiao Yang; Yunfeng Lin (Science Bulletin, 2024)

Unraveling size-dependent catalytic activity of monolithic alginate hydrogels for PMS activation and ciprofloxacin removal - Jie Lin; Yunxiong Zeng; Xingyu Zhan; Jingcai Xu; Xinqing Wang; Bo Hong; Xiaoling Peng; Jing Li; Hongwei Chen; Yingchun Xia (Journal of Environmental Chemical Engineering, 2024)

Nitrogen-doped cobalt oxide via atmospheric modulation activates PMS for rapid degradation of organic pollutants: Role of nitrogen fraction on sulfapyridine elimination - Lingxiao Zou; Kai Yang; Yihui Hu; Xingyu Guo; Xiaojing Li; Yuancai Lv; Yifan Liu; Xiaoxia Ye; Chunxiang Lin; Minghua Liu (Journal of Water Process Engineering, 2024)

Impacts of land use and crop structure change on the value of ecosystem services in Hetao Irrigation District of China - Lin Yang; Shengwei Zhang; Meng Luo; Xingyu Zhao; Xi Lin; Qian Zhang; Kedi Fang; Shengwei Lv (Journal of Cleaner Production, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Emamectin benzoate-induced toxicity affects intestinal epithelial integrity involving apoptosis - Xingyu Yue; Fengxiang Lin; Shuyan Gui; Sai Zhang; Zongbin Wu; Yuxin Xiang; Tianxiang Xiao; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food and Chemical Toxicology, 2024)

HAX1-Overexpression Augments Cardioprotective Efficacy of Stem Cell-Based Therapy Through Mediating Hippo-Yap Signaling - Wen-Feng Cai; Lin Jiang; Jialiang Liang; Suchandrima Dutta; Wei Huang; Xingyu He; Zhichao Wu; Christian Paul; Xiang Gao; Meifeng Xu; Onur Kanisicak; Junmeng Zheng; et al. (Stem Cell Reviews and Reports, 2024)
Although stem/progenitor cell therapy shows potential for myocardial infarction repair, enhancing the therapeutic efficacy could be achieved through additional genetic modifications. HCLS1-associated protein X-1 (HAX1) has been identified as a versatile modulator responsible for cardio-protective signaling, while its role in regulating stem cell survival and functionality remains unknown. In this study, we investigated whether HAX1 can augment the protective potential of Sca1 + cardiac stromal cells (CSCs) for myocardial injury. The overexpression of HAX1 significantly increased cell proliferation and conferred enhanced resistance to hypoxia-induced cell death in CSCs. Mechanistically, HAX1 can interact with Mst1 (a prominent conductor of Hippo signal transduction) and inhibit its kinase activity for protein phosphorylation. This inhibition led to enhanced nuclear translocation of Yes-associated protein (YAP) and activation of downstream therapeutic-related genes. Notably, HAX1 overexpression significantly increased the pro-angiogenic potential of CSCs, as demonstrated by elevated expression of vascular endothelial growth factors. Importantly, implantation of HAX1-overexpressing CSCs promoted neovascularization, protected against functional deterioration, and ameliorated cardiac fibrosis in ischemic mouse hearts. In conclusion, HAX1 emerges as a valuable and efficient inducer for enhancing the effectiveness of cardiac stem or progenitor cell therapeutics. Graphical Abstract

Intelligent DNA-based hydrogels: An outstanding programable and biocompatible material for food applications - Guo Li; Hao Huang; Liang Zou; Xiaochen Zhang; Xingyu Lin; Miral Javed; Xingcai Zhang; Yanqun Xu; Rong Ai; Zisheng Luo; Dong Li (Trends in Food Science & Technology, 2024)

One-pot dual-CRISPR/Cas12b-mediated dUTP-LAMP for rapid and sensitive detection of foodborne pathogens without carryover contamination - Chao Zhang; Zisheng Luo; Xingyu Lin (Food Bioscience, 2024)

Structural engineering of magnetite nanozymes for enhanced chemodynamic cancer therapy - Yong Qian; Jinglu Zou; Jiahui Zhang; Xingyu Wang; Xiangfu Meng; Yefeng Lin; Wenchu Lin; Miqin Zhang; Hui Wang (Chemical Engineering Journal, 2024)

Surface atom rearrangement enabling graphitic carbon nitride/sodium alginate gel monolith for ultrafast completely photodegrading ciprofloxacin under visible light - Xingyu Zhan; Zhilong Zhang; Jie Lin; Jingcai Xu; Xinqing Wang; Bo Hong; Yingchun Xia; Yunxiong Zeng (Chemical Engineering Journal, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Inhalation bioaccessibility of imidacloprid in particulate matter: Implications for risk assessment during spraying - Yuying Liu; Fengxiang Lin; Xingyu Yue; Sai Zhang; Han Wang; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Journal of Hazardous Materials, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

Piezo-Fenton catalysis in Fe3O4-BaTiO3 nanocomposites: A low-cost and highly efficient degradation method without the additive of H2O2 or Fe(II) ions - Jiaxing Xie; Qun Liu; Lijuan Huang; Xingyu Chen; Chunlin Zhao; Xiao Wu; Tengfei Lin; Yong Wu; Min Gao; Cong Lin (Chemical Engineering Journal, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Global response of different types of grasslands to precipitation and grazing, especially belowground biomass - Xi Lin; Hongbin Zhao; Shengwei Zhang; Vijay P. Singh; Ruishen Li; Meng Luo; Shuai Wang; Xingyu Zhao; Shengwei Lv; Xinghui Chen (Agriculture, Ecosystems & Environment, 2024)

Effects of Different pH Treatments on the Postharvest Quality of Two Kinds of Loose-Skin Citrus Fruit - Xingyu Lin; Yuxin Du; Kexin Liu; Chunmei Yin; Jiaxian He; Mingfei Zhang (Applied Fruit Science, 2024)

New modifications of PBAT by a small amount of oxalic acid: Fast crystallization and enhanced degradation in all natural environments - Qingyang Luan; Han Hu; Xingyu Ouyang; Xiaoyu Jiang; Chen Lin; Hanxu Zhu; Ting Shi; Yi-Lei Zhao; Jinggang Wang; Jin Zhu (Journal of Hazardous Materials, 2024)

Impact of time-lagging and time-preceding environmental variables on top layer soil moisture in semiarid grasslands - Ruishen Li; Shengwei Zhang; Fengming Li; Xi Lin; Meng Luo; Shuai Wang; Lin Yang; Xingyu Zhao (Science of The Total Environment, 2024)

Experimental and nonlinear analytical of the flexural performance of timber-filled steel tubular composite beams - Xingyu Song; Lin Zhao; Yan Liu; Meng Gong (Engineering Structures, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

Construction of site-specific magnetic Z-scheme CdS/Fe3O4@N-doped graphene aerogel microtube/N-doped TiO2 with porous structure: enhanced catalytic performance in photo-Fenton reaction - Ying Wang; Lirong Zhao; Xingyu Cai; Yuexing Chen; Jingyin Xu; Li Zhang; Li Lin; Xianxiang Dai; Yuanyuan Jiang; Jinqiu Liao; Yunsong Zhang (Environmental Science and Pollution Research, 2024)

Carboxymethyl cellulose-based supramolecular hydrogel with thermo-responsive gel-sol transition for temporary plugging of oil pipeline in hot work - Ziteng Yang; Ruixuan Ni; Yang Yang; Jie Qi; Xingyu Lin; Yong Zhang; Li Wang; Yuanpeng Wu; Xiaojiang Li; Hongsheng Lu (Carbohydrate Polymers, 2024)

The complete mitochondrial genome of Nephrotoma scalaris parvinotata (Brunetti 1918) (Diptera: Tipulidae) and insights into the phylogeny of Tipulomorpha - Nan Song; Qiong Wu; Xingyu Lin; Yang Zhang; Te Zhao (Journal of Asia-Pacific Entomology, 2023)

Increase in aerodynamic impedance and energy uptake in response to grazing prohibition in semi-arid grasslands during the beginning of the growing season - Ruishen Li; Shengwei Zhang; Fengming Li; Xi Lin; Shuai Wang; Lin Yang; Xingyu Zhao; Minmin Liu (Journal of Arid Environments, 2023)

In vivo-in vitro correlations (IVIVC) for the assessment of pyrethroid bioavailability in honey - Yuying Liu; Siyuan Jiang; Yuxin Xiang; Fengxiang Lin; Xingyu Yue; Minkun Li; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food Chemistry, 2023)

Morph-genetic biomimetic multiscale porous hydrogels for high-efficient solar evaporation from seawater - Lin Chen; Yue Sun; Chao Ma; Ye Sun; Shuyi Peng; Xingyu Cao; Lang Yang; Chunxin Ma; Hongliang Zhao; Hao Wang; Dong Zhang; Qijie Liu; et al. (Chemical Engineering Journal, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

pH-regulated superhydrophobic quartz sands for controllable oil-water separation - Xingyu Lin; Yong Zhang; Ziteng Yang; Wenjian Yue; Ruoxin Zhang; Jie Qi; Hongsheng Lu (Journal of Environmental Chemical Engineering, 2023)

Activation of MG53 Enhances Cell Survival and Engraftment of Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes in Injured Hearts - Ki Ho Park; Xingyu He; Lin Jiang; Hua Zhu; Jialiang Liang; Yigang Wang; Jianjie Ma (Stem Cell Reviews and Reports, 2023)
Background and Objective Our previous studies demonstrated that MG53 protein can protect the myocardium, but its use as a therapeutic is challenging due to its short half-life in blood circulation. This study aimed to investigate the cardioprotective role of MG53 on human induced pluripotent stem cell-derived cardiomyocytes (HiPSC-CMs) in the context of myocardial ischemia/reperfusion (I/R). Methods In vitro : HiPSC-CMs were transfected with adenoviral MG53 (HiPSC-CMs MG53 ), in which the expression of MG53 can be controlled by doxycycline (Dox), and the cells were then exposed to H 2 O 2 to mimic ischemia/reperfusion injury. In vivo : HiPSC-CMs MG53 were transplanted into the peri-infarct region in NSG™ mice after I/R. After surgery, mice were treated with Dox (+ Dox) to activate MG53 expression (sucrose as a control of -Dox) and then assessed by echocardiography and immunohistochemistry. Results MG53 can be expressed in HiPSC-CM MG53 and released into the culture medium after adding Dox. The cell survival rate of HiPSC-CM MG53 was improved by Dox under the H 2 O 2 condition. After 14 and 28 days of ischemia/reperfusion (I/R), transplanted HiPSC-CMs MG53 + Dox significantly improved heart function, including ejection fraction (EF) and fractional shortening (FS) in mice, compared to HiPSC-CMs MG53 -Dox, and reduced the size of the infarction. Additionally, HiPSC-CM MG53 + Dox mice demonstrated significant engraftment in the myocardium as shown by staining human nuclei-positive cells. In addition, the cell survival-related AKT signaling was found to be more active in HiPSC-CM MG53 + Dox transplanted mice’s myocardium compared to the HiPSC-CM MG53 -Dox group. Notably, the Dox treatment did not cause harm to other organs. Conclusion Inducible MG53 expression is a promising approach to enhance cell survival and engraftment of HiPSC-CMs for cardiac repair. Graphical Abstract

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Microbial community assembly responses to polycyclic aromatic hydrocarbon contamination across water and sediment habitats in the Pearl River Estuary - Wei Lin; Fuqiang Fan; Guangming Xu; Kaiyuan Gong; Xiang Cheng; Xingyu Yuan; Cheng Zhang; Yuan Gao; Shengrui Wang; How Yong Ng; Yue Dong (Journal of Hazardous Materials, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Highly efficient carbon assimilation and nitrogen/phosphorus removal facilitated by photosynthetic O2 from algal-bacterial aerobic granular sludge under controlled DO/pH operation - Zejiao Li; Jixiang Wang; Jialin Liu; Xingyu Chen; Zhongfang Lei; Tian Yuan; Kazuya Shimizu; Zhenya Zhang; Duu-Jong Lee; Yuemei Lin; Yasuhisa Adachi; Mark C.M. van Loosdrecht (Water Research, 2023)

Random forest method for analysis of remote sensing inversion of aboveground biomass and grazing intensity of grasslands in Inner Mongolia, China - Shuai Wang; Hasi Tuya; Shengwei Zhang; Xingyu Zhao; Zhiqiang Liu; Ruishen Li; Xi Lin (International Journal of Remote Sensing, 2023)

Ultrasensitive quantification of pathogens in milliliters of beverage by filtration-based digital LAMP - Yuhua Yan; Tao Yang; Zisheng Luo; Dong Li; Li Li; Xingyu Lin (Food Chemistry, 2023)

Nanoporous electrode with stable polydimethylsiloxane coating for direct electrochemical analysis of bisphenol A in complex wine media - Jingjing Wang; Jiening Yu; Yuan Yu; Zisheng Luo; Gangfeng Li; Xingyu Lin (Food Chemistry, 2023)

An ultrafast electrochemical synthesis of Au@Ag core-shell nanoflowers as a SERS substrate for thiram detection in milk and juice - Jingjing Wang; Zisheng Luo; Xingyu Lin (Food Chemistry, 2023)

Ultrafast and absolute quantification of SARS-CoV-2 on food using hydrogel RT-LAMP without pre-lysis - Tao Yang; Dong Li; Yuhua Yan; Fatima-ezzahra Ettoumi; Ricardo A. Wu; Zisheng Luo; Hanry Yu; Xingyu Lin (Journal of Hazardous Materials, 2023)

Near-Optimal Control for Offshore Structures with Nonlinear Energy Sink Mechanisms - Wei Chen; Xingyu Du; Bao-Lin Zhang; Zhihui Cai; Zhongqiang Zheng (Journal of Marine Science and Engineering, 2022)
To improve the safety and reliability of offshore structures subject to wave loading, the active vibration control problem is always one of significant issues in the field of ocean engineering. This paper deals with the near–optimal control problem of offshore structures with a nonlinear energy sink (NES) mechanism. By taking the dominant vibration mode of the offshore structure with the NES into account, a nonlinear dynamic model of the steel–jacket structure subject to wave loading is presented first. Then, using the parameter perturbation approach to solve a nonlinear two–point boundary value problem, an NES–based optimal controller with the form of infinite series sum is presented to suppress the vibration of the offshore structure. Third, an iteration algorithm is provided to obtain the near–optimal controller. Simulation results demonstrate that the NES–based near–optimal controller can mitigate the oscillation amplitude of offshore structures significantly. Moreover, the NES–based optimal controller outperforms the one based on active tuned mass damper.

Mechanisms of high-frequency dinoflagellate blooms of Scrippsiella trochoidea in Daya Bay, South China Sea - Yuan Tian; Simin Hu; Xianzhi Lin; Hui Huang; Xingyu Song; Yan Yan; Xuedong Xie; Tao Li; Sheng Liu (Journal of Oceanology and Limnology, 2021)

Metallothionein induction attenuates the progression of lung injury in mice exposed to long-term intermittent hypoxia - Xingyu Lin; Rekha Jagadapillai; Jun Cai; Lu Cai; Guoguang Shao; Evelyne Gozal (Inflammation Research, 2020)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

A remorin gene is implicated in quantitative disease resistance in maize - Tiffany M. Jamann; Xingyu Luo; Laura Morales; Judith M. Kolkman; Chia-Lin Chung; Rebecca J. Nelson (Theoretical and Applied Genetics, 2016)

Boron deficiency affects cell morphology and structure of young leaves of radish - Xinli Cong; Haiyu Jing; Nan Lin; Zhihui Xia; Mianjia Huang; Xingyu Jiang (Acta Physiologiae Plantarum, 2015)

Effects of elevated carbon dioxide concentration on nitrous oxide emissions and nitrogen dynamics in a winter-wheat cropping system in northern China - Yingchun Li; Erda Lin; Xue Han; Zhengping Peng; Wen Wang; Xingyu Hao; Hui Ju (Mitigation and Adaptation Strategies for Global Change, 2015)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

Effect of elevated carbon dioxide on growth and nitrogen fixation of two soybean cultivars in northern China - Shu Kee Lam; Xingyu Hao; Erda Lin; Xue Han; Rob Norton; Arvin R. Mosier; Saman Seneweera; Deli Chen (Biology and Fertility of Soils, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)